Análise das características do solo de Francisco Beltrão - PR e suas influências nas inundações do perímetro urbano - Minuzzo, Simone (2016)
Land occupation in Francisco Beltrão, Paraná, was carried out bearing in mind only emergency needs, without considering the impact this unplanned occupation would have on the environment and on its inhabitants. The intense urbanization process waterproofed the soil, silted the rivers and removed the riparian forests, factors that increase vulnerability to flooding. The objective of this paper has been to spatialize the results of characterization tests of 24 soil samples in thematic maps, as well as making thematic maps to characterize the relief and the use and occupation of the soil, as well as maps with the floods that occurred in 2012, 2013, 2014 and 2015. The GIS - Geographic Information System used was SPRING. In order to analyze the results, there have been several cross-checks of data between the maps. Soil classification was performed according to the Unified Classification and with the texture. Soil infiltration at 23 points was determined by the concentric ring method. Soil density, in general, showed to be more preponderant in the interferences in the infiltration rate than the soil texture. The land use and occupation map showed the high waterproofing condition of the territory and the lack of green areas to cushion the rainwater, as well as the scarcity of ciliary forest. Through the cross-linking of the map of land use and occupation with the map of hypsometry, it was verified that a constructed area corresponding to 18.75% of the urban area is located at a risk of flood area. Four maps of flood spots were obtained by recognizing the extent of flood spots in the periods of 2011, 2013, 2014 and 2015. According to the surveys, the maximum flood level determined was 548m. Crossing between the declivity map and the floodplain maps shows that the areas most affected by the floods are those with the lowest slope (0 to 3%), which total 53.58% of the flooded areas. The resulting thematic maps provide important information about the characteristics of the urban territory. The presented results can help in the planning and re-adaptation of the urban space.